Respostas
respondido por:
21
x(x + 3) = 5x + 15
x² + 3x = 5x + 15
x² + 3x - 5x - 15 = 0
x² - 2x - 15 = 0
Δ = (-2)² - 4(1)(-15)
Δ = 4 + 60 = 64
√Δ = √64 = 8
x' = (2 + 8)/2 = 10/2 = 5
x'' = (2 - 8)/2 = -6/2 = -3
Resposta: x = 5 ou x = -3
Espero ter ajudado.
x² + 3x = 5x + 15
x² + 3x - 5x - 15 = 0
x² - 2x - 15 = 0
Δ = (-2)² - 4(1)(-15)
Δ = 4 + 60 = 64
√Δ = √64 = 8
x' = (2 + 8)/2 = 10/2 = 5
x'' = (2 - 8)/2 = -6/2 = -3
Resposta: x = 5 ou x = -3
Espero ter ajudado.
ProfRafael:
Obrigado!
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás